IMPROVING STUDENTS’ WRITING DESCRIPTIVE TEXT COMPETENCE USING MAPPING PICTURES - Sutri Winurati; Sulistyaningsih Sulistyaningsih; Okky Ria Vinola (Proceeding International Conference on Digital Education and Social Science, 2022)
The aims of this study were to improve students’ competence in writing descriptive text; the researcher used classroom action research as method and the image Mapping Picture as an authentic visual media technique. The subject were the 36 students of this research in class VII-C SMP Negeri 2 Sukodono, Sidoarjo 2nd semester of academic year 2021/2022 The success indicator of this research was if there were at least 22 or (60%) students of 36 students could write descriptive English text in accordance with the rubric of descriptive writing. This study was conducted for 3 meetings. In cycle I action the students described a particular animal or plant by using Mapping Picture. In cycle II action students described public places using Mapping Picture too. Qualitative research with data analysis method showed the result that there was an increasing number of students who had reached Minimum Mastery Criteria (KKM) 75. The pre-cycle scores of the original condition only 10 or (28%) students from 36 students; and first-cycle scores, there were increased scores of 17 or 47% students and the third-cycle’s scores were 25 or (69%) students who got the Minimum Mastery Criteria (KKM) 75. The improvement was 41%. In conclusion, the students’ competence in writing descriptive text were improved by using Mind Map pictures.